Analisis Kinerja Keuangan dan Ukuran Perusahaan terhadap Harga Saham Perusahaan dalam Indeks LQ45 Di BEI dengan Regresi Data Panel - Aminar Sutra Dewi; Zusmawati Zusmawati; Nola Hasrina Lova (JURNAL PUNDI, 2018)
The stock price of companies listed in the LQ45 Index has decreased almost in all sectors, except the mining and infrastructure sectors are still in the green zone. This study aims to examine the effect of Return on Equity on stock prices and the size of the Company on the company's stock price. The sample was selected using a purposive sampling method, while the data used was secondary data in the form of financial report data. The model is estimated using data panel regression, namely Common Effects Models (CEM), Fixed Effects Models (FEM), and Random Effects Models (REM). The results of this study indicate that financial performance has no significant effect on stock prices, and the size of the company also has no significant effect on stock prices.